Challenges in the treatment of BRAF K601E-mutated lung carcinoma: a case report of rapid response and resistance to dabrafenib and trametinib - Nishiyama, Akihiro; Sato, Shigeki; Sakaguchi, Hiroyuki; Kotani, Hiroshi; Yamashita, Kaname; Ohtsubo, Koushiro; Nanjo, Shigeki; Yano, Seiji; Mizuguchi, Keishi; Ikeda, Hiroko; Takeuchi, Shinji (Frontiers in Oncology, 2024)
We report a case of limited effectiveness of dabrafenib and trametinib in a 59-year-old man with poorly differentiated lung carcinoma and a rare BRAF K601E mutation. The patient, unresponsive to chemotherapy and immunotherapy, received these targeted agents as second-line treatment. Despite a notable initial response, tumor regression lasted only 52 days. A subsequent liquid biopsy revealed additional alterations (BRAF amplification, KIT amplification, TP53 S241F), indicating a complex resistance mechanism. This case underscores the challenges in treating BRAF K601E-mutant lung carcinoma, emphasizing the need for advanced molecular diagnostics, personalized approaches, and further research into more effective therapies for unique genetic profiles.